The Internet of Things for Smart Urban Ecosystems - Cicirelli, Franco; Guerrieri, Antonio; Mastroianni, Carlo; Spezzano, Giandomenico; Vinci, Andrea (Internet of Things, Technology, Communications and Computing, 2019)
The main objective of this book is to provide a multidisciplinary overview of methodological approaches, architectures, platforms, and algorithms for the realization of an Internet of Things (IoT)-based Smart Urban Ecosystem (SUE). Moreover, the book details a set of real-world applications and case studies related to specific smart infrastructures and smart cities, including structural health monitoring, smart urban drainage networks, smart grids, power efficiency, healthcare, city security, and emergency management. A Smart Urban Ecosystem (SUE) is a people-centric system of systems that involves smart city environments, applications, and infrastructures. SUEs require the close integration of cyber and physical components for monitoring, understanding and controlling the urban environment. In this context, the Internet of Things (IoT) offers a valuable enabling technology, as it bridges the gap between physical things and software components, and empowers cooperation betweendistributed, pervasive, and heterogeneous entities.